How Effective Is Entrepreneurship Education in Schools? An Empirical Study of the New Curriculum in Spain - Núñez-Canal, Margarita; Sanz Ponce, Roberto; Azqueta Díaz De Alda, Arantxa; Montoro-Fernández, Elisabet (Education Sciences, 2024)
This research analyzes the results of an entrepreneurship education program focused on knowledge and attitudes in 1036 students of secondary education, high school, and vocational training, differentiated into two groups, control and experimental. It analyzes the outcomes after incorporating entrepreneurship content into the school curriculum and participating in a program of entrepreneurial potential, which develops creativity, leadership, personal control, achievement motivation, and problem-solving. Non-parametric statistics were used to assess the influence of the acquisition of entrepreneurial knowledge on the gender, age, school ownership, and socio-educational level of the parents. This study shows that students with a positive attitude towards entrepreneurship improve their entrepreneurial knowledge and that the impact is more significant if they participate in the specific program. The results are not significant for the variables gender, school type, and parents’ level of education, but they are significant for age and school level. The effectiveness of including content on entrepreneurship in the curriculum and the specific program is ratified. It is proposed to reinforce education in entrepreneurial knowledge that strengthens the students’ identity and future entrepreneurial intention.
Keywords: entrepreneurship education; education efficacy; attitude; quantitative assessment; competence; entrepreneurial knowledge